Nurses' experiences of participating in a randomised controlled trial (RCT) in the community - Newall, N.; Miller, C.; Lewin, Gill; Kapp, S.; Gliddon, T.; Carville, Keryln; Santamaria, Nick (Cambridge Media, 2009)
There is a dearth of experience and sharing of experiences by comunity nursing agencies in the conduct of clinical trials in the community. The objective of this research was to explore and identify the challenges and opportunities that arose when two community nursing services implemented a randomised controlled trial (RCT) in the community. An exploratory study was undertaken with the nurses responsible for implementing the trial at the operational level. Three focus froup discussions were convened with the nurses. Key themes from the data were extracted and summarised. The eight key themes emerging from the analysis of the focus group data were - being part of a trial, expectations versus the real RCT experience, benefits associated with implementing the trial, responses to the trial of other nurses not directly involved in the RCT, clients' responses to the trial experience, challenges, strategies to refine research prcesses and further involvement in research.This study offers insights into the experiences of clinicians and researchers involved in implementing a clinical trial in community settings. These include what worked well what pitfalls were and how thy might have been avoided, and strategies for organisations wishing to undertake a clinical trial or to refine their existing research processes. Additionally, some lessons for everyday practice were identified as requiring follow-up as impacting not only on the conduct of a RCT but clinical care for all times.This paper provides guidance as to how to actively involve nurses in research not just to gather data and find study recruits, but as significant contributors to decisions about research design and implementation so that they are better equipped to inform and lead future research endeavours.